Measurement of Recyclable Raw Materials Trading for Circular Economy Implementation - Mohamad Khoiru Rusydi; IDAA Warmadewanthi; Arman Hakim Nasution; Alva Edy Tontowi; Gogor Arif Handiwibowo; Gita Widi Bhawika (Institut Teknologi Sepuluh Nopember, 2023)
In the context of resource scarcity and food energy security in the midst of increasing food demand, the circular economy (CE) is a promising strategy to address the sustainable use of resources. This article aims to propose measurement elements in raw materials with recyclable concepts in implementing CE in the food and beverage industry. However, the CE framework has not been adapted to the needs of the Food And Beverages Industry. This article attempts to address this gap by analyzing the range of available indicators to measure trade in recyclable raw materials, namely by looking at the difference between the value of exports and imports. Thus, the differences in the CE framework can theoretically be adapted to the production system in the Food And Beverages Industry. So that the implementation of CE can be implemented in accordance with its functions, strategies and principles in managing a business model that replaces the concept of